ANALYZING THE EFFECTIVENESS OF ZERO-INTEREST RATE ON THE U.S. MACROECONOMY DURING THE PERIOD (2000 -2020) - Zahid Qasem Badan; Ohood Hammood Salih; Nagham Hameed Abdulkhudhur (Scholar Express Journals, 2024)
The study aimed to analyze and utilize the zero interest rate implemented by the U.S. Federal Reserve and its impact on macroeconomic variables during the period 2000-2020, using the cointegration model to address economic and financial crises facing the economy and to overcome deflationary situations caused by shocks and crises (economic downturns) such as the COVID-19 pandemic and the decline in global oil prices, among many other crises that have led to a decrease in economic growth rates. The study indicated that adopting the zero interest rate option by the United States during times of shocks and crises (economic downturns) is one of the most important tools and channels in monetary policy that directly influences the growth of economic activity and the increase in GDP growth rate through stimulating investment, activating the multiplier effect, and energizing economic sectors. The results of the time series test showed the existence of cointegration between the independent variable of zero interest rate and the dependent variables representing some macroeconomic variables (investment, unemployment, inflation, GDP). There is an inverse relationship between the zero interest rate and GDP, meaning that the zero interest rate has the ability to face economic crises and shocks (economic downturns) and to find suitable solutions within the American economy, driving economic growth forward without relying on solutions that might cause future harm to the economy, such as depending on exchange rate reductions or foreign borrowing
Keywords: Zero Interest Rate; Macroeconomics; Monetary Policy